Analysis of the Shopee’s Strategies to Succeed in the Global E-commerce Market: Malaysia Case - Madan, Sahana; Pérez-Morón, James; Chua, Xin Nee; Kee, Daisy Mui Hung; Chua, Joeanne; Chua, Ken Zie; Chuah, Yi Wen; Vidal, Luis David Santodomingo (AIBPM Publisher, 2022)
This study examines the strategies that influence consumer loyalty and buying intentions on the Shopee e-platform. Due to the rapid growth of e-commerce platforms worldwide, the researchers would like to know if this makes it difficult for Shopee to maintain customer loyalty in Malaysia. To maintain a successful existence in the global electronics market, Shopee developed integrated marketing communications, categorize the competitors, and leveraged AI and data. In this study, a total of 100 respondents from Malaysia responded to this survey. The data is collected via a survey questionnaire. The findings revealed that consumer behavior and experience, consumer convenience, and consumer trust have positively related to the customer satisfaction and purchase intent towards Shopee. Not only does this research provide Shopee with valuable guidance and insights on how customers perceive Shopee, resulting in increased customer satisfaction but also this research illustrates that Shopee has the potential to develop its prospects and strategies to succeed in the global e-commerce market.